1999
DOI: 10.1046/j.1365-2648.1999.00972.x
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation, chronic illness and disability: the missing elements in nurse education

Abstract: Chronic illnesses represent one of the most significant health challenges in all developed countries and currently there is considerable debate about how to meet the rehabilitative needs of chronically ill and disabled people. The literature suggests that nursing has a potentially significant, but largely unrealized, role to play in addressing areas of current deficit. However, to fulfil this potential it is vital that the educational preparation of nurses at both qualifying and post-qualifying levels equips t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 29 publications
0
24
1
Order By: Relevance
“…Whilst in reality self-management programmes reach comparatively few (Kralik et al, 2004), in contrast nursing has long been recognised as having a key role to play in helping people to manage chronic illness (Audit Commission, 1999, Kratz, 1978. However, there is evidence of a lack of proactive engagement with this client groups' needs (Gibbon, 1994, Kratz, 1978, Nolan and Nolan, 1995 and until recently nursing in the UK was acknowledged as not fully realising its potential to meet the needs of the chronically ill (English National Board, 1998, Nolan andNolan, 1999). In addition the nursing response to patient self-management is unclear (Wilson, 2002, Wilson, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Whilst in reality self-management programmes reach comparatively few (Kralik et al, 2004), in contrast nursing has long been recognised as having a key role to play in helping people to manage chronic illness (Audit Commission, 1999, Kratz, 1978. However, there is evidence of a lack of proactive engagement with this client groups' needs (Gibbon, 1994, Kratz, 1978, Nolan and Nolan, 1995 and until recently nursing in the UK was acknowledged as not fully realising its potential to meet the needs of the chronically ill (English National Board, 1998, Nolan andNolan, 1999). In addition the nursing response to patient self-management is unclear (Wilson, 2002, Wilson, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…As many must visit large numbers of patients every day, nurses may be adopting a task‐orientated, as opposed to a holistic, approach to care (Davy 1998). Yet another factor could be a lack of educational preparation for a role in rehabilitation (Nolan & Nolan 1999) or a lack of clinical leadership (Gibbon 1994). Finally, Goodman (2000) suggested that district nurses in particular are simply unclear over what their contribution to rehabilitation might be.…”
Section: Introductionmentioning
confidence: 99%
“…Outside the US, however, these publications seem to have had limited impact. Elsewhere, there seems to be agreement that the potential role of nurses in rehabilitation is yet to be fully realized [39-49]. To achieve this goal, the development and implementation of formal education courses could be a key strategy, making it possible to train advanced practice nurses, particularly neurorehabilitation specialists, who could fill the growing need for expert clinicians able to assume major leadership roles in clinical, management and research areas.…”
Section: Discussionmentioning
confidence: 99%